Pre-asthma: a useful concept for prevention and disease-modification? A EUFOREA paper. Part 1—allergic asthma - Scadding, G. K.; McDonald, M.; Backer, V.; Scadding, G.; Bernal-Sprekelsen, M.; Conti, D. M.; De Corso, E.; Diamant, Z.; Gray, C.; Hopkins, C.; Jesenak, M.; Johansen, P.; et al. (Frontiers in Allergy, 2024)
Several chronic diseases only become symptomatic from the moment a certain threshold of inflammation or volume of tissue damage has been reached (1-4). By this stage the disease may be irreversible with no possibility of cure (5,6). Recently the idea of earlier pre-emptive diagnosis has evolved. For example, the concept of pre-diabetes has led to identification of likely future diabetics and provision of measures to reduce disease progression. Similarly, the pre-diagnostic phase of Alzheimer’s and Parkinson's diseases are being explored in population-based studies. In this paper we explore the possibilities for similar action in asthma.